Meta-analisis bahan ajar terintegrasi materi mitigasi bencana alam terhadap kompetensi peserta didik - Robika Alkadri; Festiyed Festiyed; Asrizal Asrizal (Universitas Negeri Padang, 2019)
Indonesia is a country that is prone to natural disasters. Natural disaster mitigation has begun to be applied in Indonesia, especially in education. Disaster mitigation education in learning can be integrated in the development of integrated teaching materials on natural disaster mitigation materials. This study aims to analyze integrated teaching materials on natural disaster mitigation materials to increase the competency of students. This research uses the meta-analysis method. The first stage is the researcher formulates the research problem, then continues by tracing the existing research that is relevant for analysis. Data collection techniques using non-test is to trace the relevant thesis documents. There are 7 thesis samples used using a purposive random sampling technique. The data in this study are in the form of a percentage increase in competency. The results of this study indicate that an increase in the competency of students after using integrated teaching materials on disaster mitigation materials.